Rancang Bangun Sistem Informasi Pengajuan Kredit Berbasis Web dengan Metode Waterfall untuk Meningkatkan Efektivitas dan Efisiensi - Maharani, Novia Rahma; Sumarno, Sumarno (Journal of Information System Research (JOSH), 2025)
In the era of globalization and digitalization, the utilization of information technology has become a key factor in improving operational efficiency, including in the banking sector. Bank Perekonomian Rakyat (BPR), as a financial institution, particularly serving small and medium enterprises, faces challenges in the credit application process, which is often time-consuming and prone to errors. This manual process hinders the speed of decision-making and lowers customer satisfaction. To address these issues, the development of a Web-Based Credit Application Information System is proposed, designed to expedite and simplify the credit application process, reduce data management errors, and improve transparency and accessibility of information for customers. This system allows Account Officers (AOs) to manage customer data, verify credit eligibility, and monitor the status of applications digitally. This study uses the Waterfall method, which covers the development of the system from needs identification, design, implementation, to system evaluation. The goal of this system development is to enhance the efficiency of the credit application process, reduce potential errors in data management, and increase AO productivity in processing credit applications. The expected outcome of this research is an improvement in service quality and the competitiveness of BPR in the digital era, with a system that is more efficient, accurate, and transparent in managing credit applications.